2021
DOI: 10.3389/fmolb.2021.727847
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition Insights of Sialic Acid Glycans by Distinct Receptors Unveiled by NMR and Molecular Modeling

Abstract: All cells are decorated with a highly dense and complex structure of glycan chains, which are mostly attached to proteins and lipids. In this context, sialic acids are a family of nine-carbon acidic monosaccharides typically found at the terminal position of glycan chains, modulating several physiological and pathological processes. Sialic acids have many structural and modulatory roles due to their negative charge and hydrophilicity. In addition, the recognition of sialic acid glycans by mammalian cell lectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…Regarding the conformational behavior, Neu5Acα2-6-Gal glycosidic linkage is generally characterized by three torsion angles, defined by φ (C1-C2-O-C6'), ψ (C2'-O2'-C6-C5) and ω (O6-C6'-C5'-O5'). [31] Previous studies and energy maps demonstrated that φ could populate torsion angles of approximately À 60°and 180°, while ψ assumed a value around 180°. [31,32] On the other hand, ω gives additional flexibility to the linkage, adopting three different values in the free state, corresponding to 180°/60°/À 60°(tg/gt/gg rotamers).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the conformational behavior, Neu5Acα2-6-Gal glycosidic linkage is generally characterized by three torsion angles, defined by φ (C1-C2-O-C6'), ψ (C2'-O2'-C6-C5) and ω (O6-C6'-C5'-O5'). [31] Previous studies and energy maps demonstrated that φ could populate torsion angles of approximately À 60°and 180°, while ψ assumed a value around 180°. [31,32] On the other hand, ω gives additional flexibility to the linkage, adopting three different values in the free state, corresponding to 180°/60°/À 60°(tg/gt/gg rotamers).…”
Section: Resultsmentioning
confidence: 99%
“…[31] Previous studies and energy maps demonstrated that φ could populate torsion angles of approximately À 60°and 180°, while ψ assumed a value around 180°. [31,32] On the other hand, ω gives additional flexibility to the linkage, adopting three different values in the free state, corresponding to 180°/60°/À 60°(tg/gt/gg rotamers). In analog 1, φ torsion angle around Neu5Ac-α-(2-6)-Gal glycosidic linkage for approximately À 60°could be deduced, as suggested by the absence of NOE contacts between H6 of galactose and H3 (axial and equatorial protons) of Neu5Ac (Figure S2), that instead would have been observed if φ was 180°.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the α-(2→8)-linked dimer of Neu5Ac, all three staggered conformations were populated in MD simulations thereof using the force field 53A6 GLYC , with ψ ≈ +120°and additional excursions to −anticlinal orientations. 69 In addition to the glycosidic torsion angles in α-(2→8)linked sialic acids, 70 the exocyclic portion of the sialic acid (glycerol structural element) was analyzed with respect to the rotamer distribution of the torsion angles, ω 8 = O8−C8−C7− O7 and ω 7 = O7−C7−C6−O6, which revealed different sampling of conformational space. The former, involving the glycosidically substituted O8 atom, shows a preference for the antiperiplanar orientation, but other conformations are sampled in a more continuous fashion, although some of the eclipsed ones are not populated as anticipated (Figure 7B).…”
Section: ■ Methodsmentioning
confidence: 99%
“…In cases when a primary alcohol is glycosylated by a sugar residue an additional degree of freedom is present, e.g., in (1 → 6)-linked hexopyranosides where the torsion angle ω is related to the exocyclic hydroxymethyl group or in (2 → 9)-linked sialic acids. The definitions commonly used in solution state NMR spectroscopy of aldoses in a disaccharide are given by ϕ = H1′–C1′–O n –C n and ψ = C1′–O n –C n –H n , though other torsional angle definitions describing conformational space are in use based on IUPAC definitions or employed in studies related X-ray crystallography; n is the substitution position of the sugar residue at the reducing end and the prime refers to atoms in the terminal glycosyl entity, whereas in ketoses such as sialic acids the former torsion angle is defined by ϕ = C1′–C2′–O n –C n or ϕ = O6′–C2′–O n –C n . Furthermore, in hexopyranoses the exocyclic torsion angle ω = O5–C5–C6–O6 is the usual definition, although other definitions can be used to describe the torsion angle .…”
Section: Shape (Conformation) and Motions (Dynamics)mentioning
confidence: 99%